Relationship between work performance system and institutional performance in the context of strategic human resource management in Ministry of Education Oman / Saleh Hamood Nasser Al-Sinawi - Saleh Hamood Nasser, Al-Sinawi (2016)
Many studies have suggested that strategic management in human resource practices has an enormous effect on institutional performance. The work performance system in strategic human resource management is believed to be multidimensional and it is empirically shown to be crucial to employee’s performance. Hence, this study investigated the relationship between work performance system which includes staffing, training, involvement, compensation, performance appraisal, and caring in institutions performance of higher learning in the Sultanate of Oman. The study also examined the effects of mediator variables such as concern for customers, concern for employees, helping behavior, customer knowledge and service performance on institutional performance. A total of 531 general managers, assistant general managers and other high ranking administrators were randomly selected from the Ministry of Education of Oman. The instrument of this study contained 88 items and was constructed to assess work performance system, mediator variables and institutional performance respectively. Hypothesized relationships between work performance system, institutional performance and their mediators were then tested by using Structural Equation Modeling. Results of the analysis revealed that work performance system is significantly and positively related to the institutional performance. Moreover, the results also showed that mediator variables such as concern for employees, concern for customers, helping behavior, and service performance play a significant role in mediating between work performance system and institutional performance. This study found that concern for customers and concern for employees affect employees’ helping behavior and service performance respectively which consequently promote institutional performance. It was also found that customers’ knowledge indirectly affect institutional performance through its impact on service performance. Therefore, the iv mediation model of this present study can be used to holistically comprehend how strategic human resource management could be implemented in enhancing human resource management in Oman. Finally, the findings of this study suggested that the four mediated variables are effectively mediating between work performance system and institutional performance in human resource management.